A new species of Gekko (Squamata: Gekkonidae) from Tà Kóu Nature Reserve, Binh Thuan Province, Southern Vietnam - Tri, Ngo Van; Gamble, Tony (Zootaxa, 2010)
A new species of Gekko Laurenti is described from Tà Kóu Mountain, an isolated granitic peak in Tà Kóu Nature Reserve, Ham Thuan Nam district, Binh Thuan province, southern Vietnam. The species is distinguished from its congeners by its moderate size, with snout to vent length (SVL) reaching a maximum 107.0 mm; dorsal pattern of 5–8 white vertebral blotches between the nape and sacrum and 6–8 pairs of short white bars on the flanks; 11–14 precloacal pores in males; 14–17 longitudinal rows of smooth dorsal tubercles; and 18–20 broad lamellae beneath the fourth toe. Gekko takouensis sp. nov. is the second endemic gekkonid discovered in the Tà Kóu Nature Reserve, Cyrtodactylus takouensis Ngo & Bauer being the first.